SAT0023 Investigation of idiopathic inflammatory myopathy for shared genetic risk factors with other autoimmune disorders: Results of UK myonet. (23rd January 2014) - Jani, M.; Chinoy, H.; Lamb, J.A.; Wedderburn, L.; Vencovsky, J.; Danko, K.; Lundberg, I.; Selva O'Callaghan, A.; Radstake, T.; Platt, H.; Ollier, W.E.; Cooper, R.G.
Abstract : Background: The idiopathic inflammatory myopathies (IIM) are autoimmune disorders characterised by acquired proximal muscle weakness, inflammatory cell infiltrates in muscle biopsies and myositis-specific or associated autoantibodies. Myositis may present as a primary disorder, or may overlap with other connective tissue diseases such as rheumatoid arthritis (RA), systemic lupus erythematosus (SLE) or systemic sclerosis. The aetiology of IIM is largely unknown, but is thought to include a combination of both genetic and environmental factors. To generate ethnically homogeneous IIM cohorts of sufficient size, given the rarity of IIM, and to allow statistically meaningful research, one of the largest European IIM initiatives has enabled UK-wide ascertainment of cases with UK MYONET. Numerous recent genome-wide association studies (GWAS) have identified many genetic variants associated with autoimmune disorders, several of which are common to multiple disorders. Objectives: To test the hypothesis that genetic risk factors associated with other autoimmune disorders also predispose to IIM. Methods: SNPs significantly associated with SLE, RA, juvenile idiopathic arthritis, coeliac disease, Crohn's disease, ulcerative colitis, psoriasis, type 1 diabetes, multiple sclerosis or systemic sclerosis were identified from published Caucasian GWAS and from the national human genome research institute (NHGRI) catalogue of published GWAS. 233 unique SNPs were identified (p<5×10 -8 ), of which 99 had not been directly genotyped or captured through our MYOGEN GWAS. These SNPs were genotyped on the Sequenom platform in a sample of 391 UK Caucasian individuals with definite or probable adult or juvenile dermatomyositis or polymyositis. Genotype data was obtained from controls of European ancestry and imputation carried out for non-genotyped SNPs using HapMap Phase 3 and One Thousand Genomes data. Preliminary analysis was carried out using logistic regression in PLINK incorporating multi-dimensional scaling factors derived from the GWAS data as covariates to correct for population substructure. Results: 391 individuals and 83 SNPs were successfully genotyped and passed quality control filtering criteria. Two SNPs within the HLA region were significantly associated with IIM (rs2040406 near HLA-DQA1, p =6.21×10 -25 ; rs615672 near HLA-DRB1, p =1.65×10 -9 ). Although no SNPs outside the HLA region achieved Bonferroni corrected significance levels for the number of SNPs tested, four SNPs previously associated with RA and SLE reached nominal significance (RA: rs13315591 in FAM107A, p =0.001; SLE: rs13385731 in RASGRP3, p =0.001, rs5029939 in TNFAIP3, p =0.004; rs2230926 in TNFAIP3 ; p =0.005). Conclusions: The association of HLA SNPs confirms the autoimmune nature of IIM. The nominal association of four SNPs previously associated with SLE and RA suggests that IIM may share genetic risk factors with other autoimmune disorders. These results require confirmation in an independent replication sample. Disclosure of Interest: None Declared